IMPLEMENTATION OF THE SMART ASN APPLICATION TO IMPROVE THE QUALITY OF PERSONNEL SERVICES AT THE BADAN KEPEGAWAIAN DAERAH (BKD) OF SIDOARJO REGENCY - Pangesthu, Rizal Angger; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Smart ASN application in enhancing the quality of civil service delivery at the Regional Civil Service Agency (BKD) of Sidoarjo Regency as part of the local government’s digital transformation strategy to achieve efficient, transparent, and accessible public services. Method: The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Data analysis is guided by George C. Edward III’s policy implementation theory, which emphasizes communication, resources, implementer disposition, and bureaucratic structure as key determinants of policy success. Results: The findings indicate that BKD Sidoarjo has effectively fulfilled Edward III’s criteria by establishing clear communication channels, optimizing available resources, fostering strong implementer commitment, and developing an adaptive bureaucratic structure. Despite these achievements, several challenges persist, including data integration issues, technical barriers, and the varying adaptability of civil servants to digital systems. Novelty: This study contributes to the literature by integrating Edward III’s policy implementation theory with the practical evaluation of digital application use in regional civil service agencies at the district level, offering new insights into how localized bureaucracies adopt and adapt digital innovations to improve governance.